Fault Equivalence and Calculation Method for Distribution Networks Considering the Influence of Inverters on the Grid Side and the Distribution Network Side - Jiangang Lu; Ruifeng Zhao; Yueming Fang; Yifan Gao; Kai Gan; Yizhe Chen (Energies)
Due to the increasing availability of new energy sources, the adaptability of traditional fault analysis and calculation methods has declined when applied to distribution networks. The reason is that the traditional ideal voltage source model cannot accurately reflect the impact of new energy from the main grid side on distribution networks. Moreover, the existing calculation methods fail to consider the influence of new energy on both the grid side and the distribution network side simultaneously, resulting in relatively large calculation errors and inaccurate fault characteristics. To address the above problems, this paper first studies the control strategy and current output characteristics of typical inverter-based resources (IBR) and establishes an integrated source model for the grid side with a high proportion of IBRs during faults. The model employs a parallel connection of an ideal voltage source with series impedance and a voltage-controlled current source. A model parameter identification method is proposed, leveraging a genetic algorithm and utilizing the normal operating electrical quantities at the port. Then, a fault-equivalent model and an iterative method for calculating electrical quantities in distribution networks are proposed, based on the integrated grid-side model. The method takes into account both distributed generators (DGs) and IBRs on the grid side, using the voltage error at the point of common coupling (PCC) as the convergence criterion for the iterative calculation. The simulation results of PSCAD/EMTDC show that the proposed model and calculation method have high accuracy. The model precisely reflects the characteristics of reduced port voltage and limited current during faults on the grid side. The amplitude errors of the electrical quantities are within 1%, and the phase angle errors are within 4°.